Indonesian Future Strategic Defense Planning - Muhammad Harry Riana Nugraha (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2017)
This paper is intended to examine how strategic defense planning of Indonesia during strategic areas of Southeast Asia (ASEAN) 2015 - 2020. Issues that develop in ASEAN seems so complex and dynamic. Indonesia’s defense is an interesting phenomenon. Based on these timeframes we can formulate a strategic planning for future defense. The results show that besides, developing defense policy and defense planning in the form of comprehensive strengthening of structure and posture of Indonesia’s defense. Indonesia needs to strengthen its defense diplomacy towards countries in Southeast Asia by strengthening the base of posture and defense structure associated with the vision of the world maritime axis so as to achieve a sustainable Minimum Essential Force (MEF).